Who calls the shots in Naomi's life? Reading the Naomi-Ruth story within the African religio-cultural context (Acta Theologica)
In Africa, the whole are religious and the dead are believed to be actively involved in the daily affairs of the people. Such a worldview, in which the Sacred Other, the living and the (living) dead formed an integral whole, can also be observed at critical points in Naomi’s life: when Naomi bid farewell to her daughters-in-law (Rt 1:8-9); Naomi’s confession about Yahweh’s faithfulness to both the living and the dead (Rt 2:20); Naomi’s plan to seek security for Ruth through “levirate” marriage (Rt 3:1), and when she acted as a nurse to Mahlon’s son (Rt 4:5, 16). Basing one’s arguments on the apparent resemblances between the world view in which the narrative of Ruth is embedded and the African (Northern Sotho) world view, how may it be far-fetched to argue that the dead (males) called the shots in Naomi’s life?